Influence of Calcium Perchlorate on Organics Under SAM‐Like Pyrolysis Conditions: Constraints on the Nature of Martian Organics. Issue 7 (6th July 2020) - Millan, M.; Szopa, C.; Buch, A.; Summons, R. E.; Navarro‐Gonzalez, R.; Mahaffy, P. R.; Johnson, S. S.
Abstract: Most of the organics detected on Mars so far are aliphatic and aromatic organo‐chlorine compounds. The smallest were first identified by the thermal treatment of the solid samples by Viking in 1976; although at the time, they were attributed to contamination. Since 2012, a larger variety of structures have been identified by the Sample Analysis at Mars experiment aboard the Curiosity rover. Evidence suggests that the chlorohydrocarbons formed during pyrolysis of sedimentary materials. Laboratory experiments show that heating of samples containing oxychlorines, such as chlorates (ClO3 − ) and perchlorates (ClO4 − ), along with organic matter present at Mars' surface is the logical source of these compounds. Nevertheless, this discovery of indigenous organic matter in the Mars regolith raises important questions: How do the oxychlorines influence the pyrolysis of organics? What are the organics precursors of the organo‐chlorinated molecules detected on Mars? Is there a way to identify the parent molecules in a sample after pyrolysis? This paper presents the results of systematic laboratory experiments of the products formed during the pyrolysis of organic compounds from three chemical families—polycyclic aromatic hydrocarbons, amino acids, and carboxylic acids—in presence of calcium perchlorates. Results show that the polycyclic aromatic hydrocarbon parent molecules and most of the carboxylic acids are still detectable after pyrolysis in presence of calcium perchlorate and that the degradation and/or evolution of all parent molecules mostly depends on their chemical nature. In addition, we demonstrate that the chlorohydrocarbons detected on Mars by the Sample Analysis at Mars instrument could come from the three chemical families studied. Plain Language Summary: Organic molecules are the building blocks of life as we know it, and detecting them on the surface of Mars has been one of the major goals of Mars exploration. Viking landers in 1976, followed by the Curiosity rover in 2012, discovered simple chlorine‐bearing organics on Mars. These chlorohydrocarbons are known to be mainly produced by the instrument itself, through chemical reactions at high temperatures between other organic molecules thermally extracted from solid rock and soil samples that react with the oxidizing minerals present on Mars (e.g., perchlorates). Studying the influence of the minerals like perchlorates on the thermal extraction of different parent molecules requires thorough experimental studies like this one. Our work constrains the potential parent molecules of the chlorohydrocarbons detected on Mars in the presence of calcium perchlorate, thereby shedding light on the past and present habitability of Mars. Key Points: A systematic study reveals the influence of calcium perchlorate during the pyrolysis of organic compounds from various chemical families Some parent organics can be identified after thermal extraction as well as through the production of characteristic pyrolysis product(s) The precursors of the chlorohydrocarbons detected on Mars with the SAM instrument could originate from the three chemical families studied